Bibliometrics and scientometrics in applied linguistics: Epilogue to the special issue - Aryadoust, Vahid (Studies in Second Language Learning and Teaching, 2023)
In this paper, I first discuss the field of bibliometrics, which is a quantitative approach to analyzing scholarly publications, and its subfield, scientometrics, which focuses exclusively on scientific literature. I argue that the use of bibliometric methods has been growing in applied linguistics in recent years, and explore the common features between bibliometrics and scientometrics. I will then review the papers published in the special issue on bibliometrics in applied linguistics, which features nine papers on various bibliometric topics. I conclude with suggestions for future research in the field, including the development of scales for measuring perceived prestige, investigation of indicators of influence and a predictive theory for impact of second language (L2) research, and further investigation into the imbalance in the representation of authors based in different parts of the world.